THE INFLUENCE OF WORK ENVIRONMENT, WORK DISCIPLINE AND WORK MOTIVATION ON PRINTING EMPLOYEES WORK PRODUCTIVITY CV ADI PRIMA MEDAN - Syardiansyah, Syardiansyah; Rosalina, Dhian; Mazaya, Syarah Nur (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2023)
This study aims to determine the effect of work environment discipline and work motivation on employee productivity at CV Printing Adi Prima. This study used a sample of 35 respondents who were temporary employees or freelancers from CV Printing Adi Prima. The data analysis method used linear regression equation multiple, t test and coefficient of determination ( R2). The results for the equation, Y= 0.802 + 0.226 X1 +0.336 X2 +0.192 X3, a constant of 802 is Employee Work Productivity when the variable influence of Work Environment Work Discipline and Work Motivation is zero, the regression coefficient is 0.226 X1 +0.336 X2 +0.192 X3 , shows that the work environment of work discipline and work motivation has a positive effect on employee productivity and if the work environment of work discipline and work motivation increases by one unit, it will increase employee productivity by 802. The results of the t test, t sig < 5% (0.000 < 0 0.05) it can be stated that the work environment, work discipline and work motivation have a significant effect on employee productivity at CV Printing Adi Prima. The results of the coefficient of determination (R2) obtained 0.448 or 44.8% Work Environment variables Work Discipline and Work Motivation affect Work Productivity of Adi Prima CV Printing employees and 0.552 or 55.2% influenced by other variables not examined in this study.